Endothelial Cells and Astrocytes: A Concerto en Duo in Ischemic Pathophysiology. (28th May 2012) - Berezowski, Vincent; Fukuda, Andrew M.; Cecchelli, Roméo; Badaut, Jérôme
Abstract : The neurovascular/gliovascular unit has recently gained increased attention in cerebral ischemic research, especially regarding the cellular and molecular changes that occur in astrocytes and endothelial cells. In this paper we summarize the recent knowledge of these changes in association with edema formation, interactions with the basal lamina, and blood-brain barrier dysfunctions. We also review the involvement of astrocytes and endothelial cells with recombinant tissue plasminogen activator, which is the only FDA-approved thrombolytic drug after stroke. However, it has a narrow therapeutic time window and serious clinical side effects. Lastly, we provide alternative therapeutic targets for future ischemia drug developments such as peroxisome proliferator- activated receptors and inhibitors of the c-Jun N-terminal kinase pathway. Targeting the neurovascular unit to protect the blood-brain barrier instead of a classical neuron-centric approach in the development of neuroprotective drugs may result in improved clinical outcomes after stroke.